Structure of the O‐Glycosylated Conopeptide CcTx from Conus consors Venom. Issue 3 (27th December 2012) - Hocking, Henry G.; Gerwig, Gerrit J.; Dutertre, Sébastien; Violette, Aude; Favreau, Philipe; Stöcklin, Reto; Kamerling, Johannis P.; Boelens, Rolf
Abstract The glycopeptide CcTx, isolated from the venom of the piscivorous cone snail Conus consors, belongs to the κA‐family of conopeptides. These toxins elicit excitotoxic responses in the prey by acting on voltage‐gated sodium channels. The structure of CcTx, a first in the κA‐family, has been determined by high‐resolution NMR spectroscopy together with the analysis of its O‐glycan at Ser7. A new type of glycopeptide O‐glycan core structure, here registered as core type 9, containing two terminal L‐galactose units {α‐L‐Galp‐(1→4)‐α‐D‐GlcpNAc‐(1→6)‐[α‐L‐Galp‐(1→2)‐β‐D‐Galp‐(1→3)‐]α‐D‐GalpNAc‐(1→O)}, is highlighted. A sequence comparison to other putative members of the κA‐family suggests that O‐linked glycosylation might be more common than previously thought. This observation alone underlines the requirement for more careful and in‐depth investigations into this type of post‐translational modification in conotoxins.